Bile ductular reactions in the liver: similarities are only skin deep1. Issue 3 (22nd April 2019) - Alison, Malcolm R; Lin, Wey‐Ran
Abstract: Extensive bile ductular reactions (DRs) accompany many cholestatic liver diseases such as primary biliary cholangitis and primary sclerosing cholangitis (PSC) as well as parenchymal liver cell diseases such as alcoholic liver disease, non‐alcoholic steatohepatitis and HCV and HBV infections. DRs originate from bile ducts or hepatocytes after damage and can be identified by expression of markers associated with cholangiocytes, often being associated with disease progression and fibrosis. In a recent issue of The Journal of Pathology, Govaere et al employed high‐throughput RNA sequencing to compare the transcriptomic profiles of DR cells from liver diseases of different aetiology; HCV infection affecting hepatocytes and PSC initially affecting biliary epithelial cells. Both DR transcriptomes were markedly different from that of their neighbouring hepatocytes and 330 genes were significantly differently expressed between the DRs of the HCV and PSC liver diseases. Exploring such gene expression profiles could enable therapeutic targeting of DRs, on the one hand to inhibit liver fibrosis and inflammation and conversely to promote hepatocyte and cholangiocyte regeneration. Copyright © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd. Abstract : Linked Article: Govaere et al. J Pathol 2019; DOI:https://doi.org/10.1002/path.5228